Mixed medullary—papillary thyroid carcinoma with mixed lymph node metastases: A case report. Issue 5 (24th May 2021) - Guerreiro, Vanessa; Costa, Cláudia; Oliveira, Joana; Santos, Ana Paula; Farinha, Mónica; Jácome, Manuel; Freitas, Paula; Carvalho, Davide; Torres, Isabel
Abstract: Mixed medullary‐follicular‐derived carcinoma is a very rare event. It is extremely important to make the correct diagnosis, due to prognostic and treatment implications. A genetic study of these patients is advisable to exclude the presence of MEN 2. Abstract : Mixed medullary‐follicular‐derived carcinoma is a very rare event. It is extremely important to make the correct diagnosis, due to prognostic and treatment implications. A genetic study of these patients is advisable to exclude the presence of MEN 2.